Tepuk Tepung Tawar Pengantin Baru sebagai Tradisi Budaya Melayu dan Media Pendidikan - Indah Septi Rahayu; Lestari Setia Ningsih (Multiverse: Open Multidisciplinary Journal, 2023)
Fresh flour holds significant cultural importance for several tribes in Indonesia, often used in traditional ceremonies such as weddings, childbirth, circumcision, and pilgrimage. This practice has its roots in Hindu rituals and was further influenced by the introduction of Islamic teachings brought by Gujarat and Hadramaut traders in the 7th century AD. These animist and vitalistic traditions, intertwined with Hinduism, continue to hold a strong presence in society. The purpose of this ceremony is to seek protection from danger, ward off misfortune, and gain blessings from deities and supernatural forces. The ritual involves the use of leaves and water, often fragranced with substances like kaffir lime, potpourri, or roses. Rice and paddy, mixed with salt and turmeric, are also sprinkled on individuals as part of the ceremony. Additionally, this tradition serves as a means of preserving cultural heritage, passed down through generations. However, there are differing views regarding this practice, with some considering it an act of shirk due to the belief in the supernatural powers associated with the objects used in the flour ritual. In Aceh, for example, plain flour is utilized in planting rituals, believed to bring good luck and provide sustenance. As a result, plain flour holds significant influence as it can impact an individual's faith and beliefs.